2022
DOI: 10.1177/10442073221130528
|View full text |Cite
|
Sign up to set email alerts
|

Policy and Practice Considerations to Support College and Career Readiness for Youth With Disabilities: A Systematic Mixed Studies Review

Abstract: Youth with disabilities must be college and career ready to be prepared for adult life. Policy efforts confirm this prioritization (Every Student Succeeds Act [ESSA], 2015; Individuals with Disabilities Education Improvement Act [IDEIA], 2004). Parallel to the emergence of college and career readiness (CCR), transition planning and service requirements have promoted successful transitions to postschool education, employment, and community living (IDEIA, 2004). However, not all high schools provide a range of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Concurrently, the team conducted a mixed studies systematic literature review across scholarly and gray literature (Mazzotti et al, 2021). Findings revealed the five domains had a range of coverage across the literature with gaps identified between research, policy, and practice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrently, the team conducted a mixed studies systematic literature review across scholarly and gray literature (Mazzotti et al, 2021). Findings revealed the five domains had a range of coverage across the literature with gaps identified between research, policy, and practice.…”
Section: Methodsmentioning
confidence: 99%
“…Students with disabilities benefit from access to and inclusion in general education (McLeskey et al, 2012; Sabornie et al, 2006). Specifically, correlational evidence indicates that more time in general education is positively related to enrollment in postsecondary education and a greater likelihood of employment after high school (Lombardi et al, 2013; Mazzotti et al, 2021; Rojewski et al, 2015). For the purpose of the current study, we focused on youth with disabilities who spend the majority of their school day with their peers without disabilities in general education settings.…”
mentioning
confidence: 99%
“…Participation in community experiences is associated with important long-term postsecondary outcomes, including employment and postsecondary education (Mazzotti et al, 2022). The Individuals with Disabilities Education Improvement Act (2004) recommends individualized education program (IEP) teams to consider how community experiences can help meet the students’ secondary transition goals.…”
Section: Importance Of Meaningful Community Inclusionmentioning
confidence: 99%
“…Participation in community experiences is associated with important long-term postsecondary outcomes, including employment and postsecondary education (Mazzotti et al, 2022)…”
Section: Importance Of Meaningful Community Inclusionmentioning
confidence: 99%
“…This includes ensuring that secondary education reform efforts align with secondary special education and transition to support students with and without disabilities (Morningstar et al, 2012). Early frameworks for college and career readiness (CCR) did not include a specific focus on students with disabilities (Conley, 2007), but recent frameworks have suggested that CCR efforts should include students with disabilities (Mazzotti et al, in press; Morningstar et al, 2017). In addition to frameworks focused on preparing students for college and careers, a number of strategies have been suggested to help ensure students have these skills.…”
mentioning
confidence: 99%